Implementasi Metode Rule-Based dalam Sistem Pakar Pemilihan Program Studi Menggunakan Bahasa Prolog - Faza, Sharfina; Rizka, Ade; Husna, Meryatul; Anugrahwaty, Rina; Fawwaz, Insidini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The alignment between study programs and students' interests and abilities is a crucial factor in academic success at the university level. Unfortunately, many prospective students face confusion when choosing majors due to limited knowledge about the characteristics of each program and its relationship with career prospects, potentially affecting their academic performance and career paths. To address this challenge, our research presents a solution in the form of a rule-based expert system developed using Prolog language. This system is designed to provide study program recommendations through analysis of user responses to various structured questions. Using score calculation methods and matching against established value parameters, the system can propose the most relevant majors among four options: Computer Engineering (CE), Information Management (MI), Multimedia Graphics Engineering Technology (TRMG), and Software Engineering Technology (TRPL). Through this implementation, prospective students receive recommendations aligned with their potential and interests, facilitating more accurate decision-making. In addition to functioning as an assistive instrument in career and academic counseling for high school students, this research also lays the foundation for the development of more sophisticated expert systems with enhanced assessment weights and precision levels in the future.